2011
DOI: 10.5005/jp-journals-10024-1054
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Handwriting, Drawing Skills and Dental Skills of Junior Dental Students

Abstract: Learning fine motor skills is a pre-requisite for succeeding in dental practice and it is sometimes challenging for dental students. Most of the methods used in the selection process depend on evaluation of intellectual ability or structured interview while manual competence is not. However, no test on aptitude or manual dexterity is used as criteria. Objective:The purpose of the present study intended to evaluate the fine motor skills of beginning dental students which could in turn be used as a method of sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…Additionally, students who perform very well in the practical courses might have average performance in the academic courses. This also indicates that the students’ manual skills impact their performance in the practical sessions, which confirms what previous investigators found about correlations between handwriting, wire bending, and waxing skills, and the practical performance of dental students 6,7,17,18 1 …”
Section: Discussionsupporting
confidence: 89%
“…Additionally, students who perform very well in the practical courses might have average performance in the academic courses. This also indicates that the students’ manual skills impact their performance in the practical sessions, which confirms what previous investigators found about correlations between handwriting, wire bending, and waxing skills, and the practical performance of dental students 6,7,17,18 1 …”
Section: Discussionsupporting
confidence: 89%
“…They stated that computer technology used exclusively as a mode of teaching and learning cannot become a substitute for interactive methods, which emphasize human‐to‐human interaction. Connections between art and dental education were also discussed by Al‐Johany 53 and Anyanwu 11 …”
Section: Resultsmentioning
confidence: 99%
“…Of the 10 studies, five were performed in USA, 3,5,6,8,9 one in Europe, 10 one in Hong Kong, 11 one in Israel, 12 one in Thailand, 4 and one in Saudi Arabia. 13 The 10 included studies were observational cohort studies. From the compiled articles a total number of 1975 participants were included in this systematic review.…”
Section: Studies Characteristicsmentioning
confidence: 99%
“…8 One study used interview questionnaires. 4 Other studies used different exercises related to manual dexterity like O'Connor Tweezer Dexterity test, 12 tactile discrimination of texture, 10 cavity preparation test, 4 Handwriting and Drawing Test, 13 Novel Object Cross-Section Test, 9 and block carving test. All the 10 studies are of cohorts ones, "a" indicates representativeness of the exposed cohort, "b" selection of the nonexposed cohort, "ascertainment of exposure, "d" demonstration that outcome of interest was not present at start of study, "e & f" comparability" assessment of outcome, "h" Was follow-up long enough, "i" adequacy of follow up of cohorts.…”
Section: Studies Characteristicsmentioning
confidence: 99%